Telemedicine as support for primary care referrals to neurologists: decision-making between different specialists when guiding the case over the phone - MANTESE, Carlos Eduardo; AQUINO, Emanuelle Roberta da Silva; FIGUEIRA, Mariana Duque; RODRIGUES, Livia; BASSO, Josue; RAUPP DA ROSA, Priscila (Arquivos de Neuro-Psiquiatria, 2021)
Background: Brazil’s public health system, the largest in the world, faces great challenges in establishing access to specialized care for all Brazilians. “Regula Mais Brasil” is a structuring project from the Ministry of Health that aims to optimize the referral process for specialized care throughout Brazil and uses telemedicine to support primary care physicians. The high demand for support and referrals in the neurology specialty raises questions about what the difficulties and doubts in managing these patients are and whether the training of the coordinating physician influences the orientation and outcome of referral. Methods: In a retrospective analysis on a database, all teleconsultations in the neurology specialty were evaluated. The diagnoses were categorized using the ICD-10 and according to the specialty of the coordinating teleconsultant for multiple comparisons. Results: In total, 1687 teleconsultations were conducted between January 10 and December 2, 2019, in the cities of Belo Horizonte and Porto Alegre and in the Federal District. The most frequent area of doubt for doctors was about epilepsy. After discussion via telemedicine, 25% of the referrals were avoided and the specialty of the teleconsultant physician did not impact the decision made: 72.3, 72.6 and 66.5%, in relation to approval by neurologists, family doctors and other experts, respectively. Conclusion: Increasing access to specialists, not only for patients but also for doctors, helps in achieving early resolution of issues of greater difficulty for primary healthcare doctors, thus resulting in lower numbers of referrals.
Keywords: Telemedicine; Health Services Accessibility, Health Equity; Primary Health Care; Neurology